Electrocardiographic findings in Coronavirus Disease-19 and its correlation with clinical severity of disease - Mumtaz Ali Khan; Anindita Menon; B S Nagaraja (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Most data on electrocardiographic (ECG) changes in patients with coronavirus disease-19 (COVID-19) have been presented without comparison to patients with other acute respiratory illnesses. The correlation of ECG changes with disease severity has also not been studied. Subjects and Methods: We compared forty COVID-19-positive and forty COVID-19-negative patients in terms of clinical presentation, ECG at admission, and cardiac biomarkers. Statistical analysis was presented as frequency (percentage) and continuous as mean ± standard deviation. Chi-square test/Fischer's exact test was used. Results: Mean age overall in the study was 52.4 ± 16 years, 67.5% data were males. About 87.5% of the COVID-positive patients and 70% of the COVID-negative patients had ECG changes at baseline. Sinus tachycardia was seen in 45% (18/40) of COVID-positive patients. About 95% (38/40) of COVID-19 positive patients had normal axis, 5% (2/40) had supraventricular tachycardia, 2.5% (1/40) had premature atrial contractions (PACs), and 7.5% (3/40) had premature ventricular contractions. One patient had ventricular bigeminy. About 7.5% (3/40) of COVID-positive cases had complete right bundle branch block (RBBB), one had complete left bundle branch block (LBBB), whereas one had incomplete LBBB. About 7.5% (3/40) of COVID-positive cases had ST-segment elevation, one of whom also developed postmyocardial infarction left ventricular thrombus. About 15% (6/40) had nonST-segment elevation acute coronary syndrome. Conclusions: COVID-19 patients have ECG changes of left-sided heart disease (PACs and LBBB) and right-sided disease (RBBB, right axis deviation, and right ventricular strain pattern) at presentation, however, right heart changes predominate. COVID-19 patients had a higher occurrence and a wider variety of ECG changes at presentation than other acute respiratory illnesses and these changes correlate well with clinical disease severity as does troponin I level.